New records of assassin bugs (Hemiptera: Heteroptera: Reduviidae) for the Dominican Republic - Daniel E. Perez-Gelabert (Novitates Caribaea, 2023)
The Hispaniolan fauna of Reduviidae is only partially known, as it has never been the subject of a comprehensive taxonomic or faunistic inventory. These species belong to Neotropical genera that have Caribbean, Central and South American distributions. In this contribution new records are given for 14 species of assassin bugs belonging to six subfamilies. Among these, seven species are first records from the Dominican Republic and the island of Hispaniola: Bactrodes spinulosus Stål, 1862 (Bactrodinae), Lophoscutus rideri Kormilev, 1988, Lophoscutus rugosipes (Guérin-Méneville, 1857) both belonging to Phymatinae, Leogorrus pallipes Stål, 1872 (Reduviinae), and the Saicinae species Oncerotrachelus nasutus (Bergroth, 1913), Tagalis drakkar Varela & Melo, 2017 and Tagalis grossi Gil-Santana, 2011. With these new records the reported extant fauna of Hispaniolan Reduviidae reaches a total of 46 documented species, which are classified in 25 genera and 10 subfamilies. Additionally, 13 fossil species have been reported from the Dominican amber.